Framework for Interactive M3 Visualization of Microscopic Traffic Simulation. Issue 44 (December 2018) - Yang, Hong; Shen, Yuzhong; Hasan, Mahmud; Perez, Daniel; Shull, John
Full comprehension of microscopic traffic simulation (MTS) models has necessitated the development of proper visualizations. Existing MTS models only provide limited capability of two- and/or three-dimensional displays that often restrict users' viewpoint to a flat screen. Their downscaled scenes neither provide a realistic representation of the environment nor allow different users to simultaneously experience the simulation model from different perspectives. This largely prevents analysts from effectively demonstrating and disseminating their simulation results to various stakeholders of different background and knowledge. In light of these issues, this paper aims to develop a framework that enables a multi-user, multi-perspective, and multi-mode ( M 3 ) visualization architecture for microscopic traffic simulation. The proposed framework is empowered by the latest advances in cloud computing and virtual reality (VR) to support interactive and immersive visualization for simulated traffic environments. A client-server architecture allows multiple users at distributed physical locations to view the same simulation from multiple perspectives simultaneously and supports a variety of virtual/augmented reality devices. A prototype of the proposed M 3 visualization framework is implemented and demonstrated by simulating and visualizing a model of typical traffic operations in a high-density urban area. The promising capability of the M 3 visualization framework is attested. Potential improvements over the present study to further excel current visualization framework are also discussed.